Chemical constituents from the fruits of Cullen corylifolium (L.) Medik. by the targeted separation mode. Issue 7 (3rd April 2021) - Liu, Xiangyue; Yang, Jing; Yu, Huijuan; Zhang, Jing; Du, Jie; Wang, Xinhui; Wang, Yuefei; Chai, Xin
Abstract: Two new compounds, corylifol H (1 ) and epi -bavacoumestan C (2 ), together with a new natural product named 8-geranyl daidzein (3 ), were isolated from the fruits of Cullen corylifolium (L.) Medik. (syn. of Psoralea corylifolia L.) by the targeted separation mode. The structures of these compounds were elucidated on the basis of spectroscopic methods and by comparison with literature properties. The anti-inflammatory effects of the two new compounds were also evaluated by activity assay in vitro . The results showed that compounds 1 and 2 inhibited nitric oxide production in LPS-activated RAW 264.7 macrophages in a dose dependent manner. Graphical Abstract: